Least-cost seed potato production in Ethiopia - Tufa, Adane H.; Meuwissen, M.P.; Lommen, W.J.; Tsegaye, A.; Struik, Paul C.; Lansink, A.G.O. (Springer, 2015)
Improved potato varieties can increase potato yields of smallholders, and thus contribute to food security improvement in Ethiopia. However, the uptake of these varieties by farmers is very limited so far and this is one of the causes of insufficient seed quality in the seed potato system in Ethiopia. The low uptake may be related to the high costs of recommended production methods for these varieties. The objective of this study was to formulate least-cost seed potato production methods for farmers in Ethiopia. The paper used integer linear programming to determine these least-cost seed potato production methods, using published data on the perceived contributions to seed tuber yield and quality of different cultivation and post-harvest management options, and calculated seed potato production cost data for the different options. For the potato-growing districts Jeldu and Welmera, several seed potato production methods were formulated from which farmers can choose an affordable method that will enable them to produce seed potato with reasonable yield and quality levels. Results showed that yield and quality levels could be simultaneously improved at relatively low extra costs, for example, by applying recommended fertilizer rate combined with two fungicide applications. In both districts, most methods were robust to 50% increases in the rental values of land, prices of seed, wage rates, and prices of agrochemicals. Findings can be used by potato development practitioners to advise farmers on the adoption of seed potato technologies that are compatible with their financial resources.